2009
DOI: 10.1590/s0004-282x2009000500014
|View full text |Cite
|
Sign up to set email alerts
|

Verbal language spontaneous recovery after ischemic stroke

Abstract: -Objective: To analyze the spontaneous recovery of the verbal language on patients who have had an ischemic stroke. Method: Retrospective analysis of 513 medical records. We characterize referring aspects for data identification, language deficit, spontaneous recovery and speech therapy. Results: The average age was 62.2 years old (SD= ±12.3), the average time of academic experience was 4.5 years (SD=±3.9), 245 (47.7%) patients presented language disturbance, 166 (54.0%) presented spontaneous recovery, from wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
7
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 20 publications
1
7
0
Order By: Relevance
“…The objective of this study was to characterize stroke patients by observing the prevalence of communication disorders and subsequent speech therapy rehabilitation follow-up, which failed to reveal significant differences of stroke between sexes; it also confirms the findings in recent studies (16,17) , especially those with detailed description of the studied population and that originated from services with similar characteristics (16,17) , even though other studies have shown a predominance of male (18) or female (19) patients. The stroke most commonly affects adult population, especially from their sixth decade of life onwards, which was proven by some studies (17) and contradicted by others (20,21) .…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…The objective of this study was to characterize stroke patients by observing the prevalence of communication disorders and subsequent speech therapy rehabilitation follow-up, which failed to reveal significant differences of stroke between sexes; it also confirms the findings in recent studies (16,17) , especially those with detailed description of the studied population and that originated from services with similar characteristics (16,17) , even though other studies have shown a predominance of male (18) or female (19) patients. The stroke most commonly affects adult population, especially from their sixth decade of life onwards, which was proven by some studies (17) and contradicted by others (20,21) .…”
Section: Discussionsupporting
confidence: 83%
“…Hypertension, on the other hand, is representatively correlated to stroke in different age groups (22) . High blood pressure was the most commonly found chronic disease occurring alone in the research patients (Table 2), which proves the importance of actions aimed at preventing that specific risk factor, since it is associated to several comorbidities (17) . However, in studies with multivariate analysis models, diabetes mellitus was mostly associated to aphasia in the surviving patients (23) , possibly because the disease course is longer than those in cardiovascular diseases.…”
Section: Discussionmentioning
confidence: 73%
See 2 more Smart Citations
“…Findings related to speech deficit on elderly patients with neurological sequelae deficit showed 47.7% of prevalence. 9,14 The deficits described in the literature refer to changes in speech fluency, hesitations, interjections and corrections which increase with advanced age. [15][16][17][18] Although contradictory, the observed changes in elderly's speech, such as reduced use of complex grammatical structures, verbiage, ambiguous use of benchmarks, the central topic digression, repetition of ideas, overinterruptions, hardship lexical access, overlapping voices, shift work changes, hesitations and repetitions can compromise the cohesion and coherence of the speech, justifying the decline of communication aspects perceived by elderly.…”
Section: Discussionmentioning
confidence: 99%